Caracteristicas del empreendedor en el acto de empreender - Dutschke, Georg (2011)
This work includes an exploratory analysis on the factors that characterize the creators of companies, both those who have consolidated the project and those entrepreneurs who failed their desire to consolidate and develop the company over time. Both cases of companies that had to close and companies that remain successful in the marketplace are considered. It has been an added issue locating the creators of companies that do not currently exist. This work is a continuation of others, developed in previous years. The methodology used was the Rasch model. Main conclusion being presented is that most factors characterizing the entrepreneurial spirit are personal values, allowing developing and undertake a project, independently of its success or not.